Encyclopedia of life science - Cullen, Katherine E. (New York : Facts On File, 2009)
Presents over two hundred alphabetically arranged entries on fundamental concepts, principles, theories, biographies, sub-disciplines, common methods, and techniques relevant to life sciences, with twelve essays, illustrations, and historical perspectives on the scientists who contribute to the field.
Feature essays: The colony collapse disorder crisis for honeybees / by Zachary Huang -- Bioinformatics : sequence alignment algoriths / by Jason S. Rawlings -- Structure-function relationships in life science / by Lisa M. Dorn -- Partners in protection : cooperative approaches to protecting wide-ranging species / by Rachel Mazur -- The effects of global change on tropical forests / by Kenneth J. Feeley -- Adaptation or not : how to tell the difference / by James Wagner -- Gene therapy and cystic fibrosis / by Caleb Hodson -- Epigenetics : regulation above the genome / by Alexandra Silveira -- The biology of ADHD / by Peggy Shadduck Palombi -- The childhood obesity epidemic / by Sharon Brown -- Model organisms for life science research / by Michael L. Goodson -- Stem cells : the next major medical breakthrough? / by Jacob P. Harney.
Includes bibliographical references and index.
Keywords: Life sciences -- Encyclopedias, Juvenile; Sciences de la vie -- 2